Packaging adhesive film and preparation method and application thereof

By adding hydrolysis, PID and modified alkali masterbatches to the packaging film and performing surface modification, the simplicity and corrosion resistance of single-layer low-grain packaging film are solved, and high pre-crosslinking and photovoltaic module performance are improved.

CN119799189APending Publication Date: 2025-04-11CYBRID TECH(ZHEJIANG) INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411973494.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to provide a single-layer low-weight packaging film with a simple process and suitable for 0BB film sealing technology. The addition of traditional acid-resistant and corrosion-resistant alkaline substances in the low-grain composite film can easily lead to film holes.

Method used

By adding anti-hydrolysis masterbatch, anti-PID masterbatch and modified alkali masterbatch to the encapsulated adhesive film, the hydrolysis of the EVA substrate is slowed down, the anti-PID performance of the adhesive film is improved, and the surface modification of the alkali masterbatch is improved to improve its compatibility with the substrate and avoid holes.

Benefits of technology

The high pre-crosslinking degree of the adhesive film (49-54%) is achieved, the fluidity and adhesion performance of the adhesive film is maintained, and the overall performance of the photovoltaic module is significantly improved, including the attenuation of PID192h is only 0.9-1.3%, the attenuation of TC200h is 1.2-2.3%, the DH1000h welding tape has no yellowing phenomenon, and the component EL has no shadow.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0005219942370000021
    Figure BDA0005219942370000021
  • Figure BDA0005219942370000071
    Figure BDA0005219942370000071
Patent Text Reader

Abstract

The invention relates to a packaging adhesive film and a preparation method and application thereof, and the packaging adhesive film is prepared from the following raw materials in parts by weight: 95-100 parts of base material resin, 0.5-2.5 parts of anti-PID master batch, 0.5-3 parts of anti-hydrolysis master batch, 0.5-2 parts of modified alkali master batch, 0.3-1 part of cross-linking agent and 0.8-2 parts of assistant cross-linking agent. The anti-hydrolysis master batch, the anti-PID master batch and the modified alkali master batch are added into the packaging adhesive film, so that the hydrolysis of the EVA substrate is slowed down, the generation of acidic substances is reduced, and the anti-PID performance of the adhesive film is improved. Meanwhile, a synergistic effect exists between the anti-hydrolysis agent and the alkaline master batch, so that acidic substances generated by hydrolysis can be further absorbed, the overall acidity of the adhesive film is reduced, and corrosion to a battery and a welding strip is reduced. The alkali master batch is subjected to surface modification, so that the compatibility of the alkali master batch and a matrix is improved, and a hole breaking phenomenon caused by particle aggregation in a low-gram-weight adhesive film is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of packaging films, and in particular to a packaging adhesive film and a preparation method and application thereof. Background Art

[0002] 0BB coating technology is a series welding solution for busbarless modules in the photovoltaic industry. Specifically, 0BB stands for "busbarless" technology, and BB stands for Busbar, which is the main grid on photovoltaic cells. 0BB technology reduces or eliminates the number of busbars to improve the photovoltaic conversion efficiency of the cell and reduce costs.

[0003] The core of 0BB lamination technology is to use the stickiness of the adhesive film to achieve the series connection of components. This technology uses hot pressing to connect the adhesive film and the soldering tape to the battery cell at the same time or in combination. There are differences in the specific implementation methods, but the basic principles are similar.

[0004] When the 0BB coating solution is implemented, the cells, solder strips, and adhesive films are usually stacked in the order of battery cells, solder strips, and adhesive films. The adhesive properties of the adhesive film in a heated state are used to fix the solder strips in a specified position while the adhesive film is bonded to the cells, completing the connection of the cells, solder strips, and adhesive films at one time. During the lamination process, the solder strips are fixed while not flowing to the bottom of the solder strips. During the use of the components and accelerated aging, good adhesion is maintained. At the same time, for TOPCON cells, potential induced decay, or PID, cannot be caused or aggravated, and grid lines and solder strips cannot be corroded. In addition, traditional acid-resistant and corrosion-resistant alkaline substances are mostly in powder form. When added to low-gram-weight coatings, they are easy to agglomerate and cause holes in the adhesive film. This technology can not only reduce processes and costs, but also improve the optoelectronic performance and reliability of components.

[0005] CN118027826A discloses a 0BB encapsulation film, which includes a pre-crosslinked layer and a water-blocking and PID-resistant layer. It has a double-layer film structure and a larger weight. Compared with the double-layer film, the single-layer film has certain advantages in cost, process simplification, equipment compatibility and photoelectric performance. The double-layer film is more complex in structure, has higher cost and process requirements, and has a lower overall crosslinking degree and is not suitable for coating technology.

[0006] CN117701189A discloses a low-weight adhesive film for busbar-free photovoltaic modules, but its anti-corrosion agent needs to be prepared by reacting styrene in a nitrogen atmosphere, and the process is relatively complicated.

[0007] Therefore, how to provide a single-layer low-weight packaging film with simple process and suitable for 0BB film sealing technology has become a problem that needs to be solved urgently. Summary of the invention

[0008] In order to solve the above technical problems, the present invention provides a low-weight packaging film. By adding anti-hydrolysis masterbatch, anti-PID masterbatch and modified alkali masterbatch into the packaging film, the PID192h attenuation of the prepared packaging film is only 0.9-1.3%, the TC200h attenuation is 1.2-2.3%, the DH1000h welding strip has no yellowing phenomenon, the component EL has no shadow, and the pre-crosslinking degree of the film can reach 49-54%, which not only maintains the fluidity and bonding properties of the film, but also improves the overall performance of the photovoltaic module.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a packaging film, wherein the raw materials for preparing the packaging film include the following components in parts by weight:

[0011]

[0012] The base resin may be 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or 100 parts, etc.

[0013] The anti-PID masterbatch may be 0.5 parts, 1 parts, 1.5 parts, 2 parts or 2.5 parts, etc.

[0014] The anti-hydrolysis masterbatch may be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts.

[0015] Among them, the modified alkali masterbatch can be 0.5 parts, 0.8 parts, 1 part, 1.3 parts, 1.5 parts, 1.8 parts or 2 parts, etc.

[0016] The cross-linking agent may be 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 part, etc.

[0017] The amount of the auxiliary cross-linking agent may be 0.8 parts, 1 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts or 2 parts.

[0018] The present invention provides a low-weight packaging film. On the one hand, by adding anti-hydrolysis masterbatch, anti-PID masterbatch and modified alkali masterbatch to the packaging film, the hydrolysis of the EVA substrate is slowed down, the generation of acidic substances is reduced, and the anti-PID performance of the film is improved. At the same time, there is a synergistic effect between the anti-hydrolysis agent and the alkaline masterbatch, which can further absorb the acidic substances generated by hydrolysis, reduce the overall acidity of the film, and reduce corrosion to batteries and welding strips. On the other hand, by surface modification of the alkali masterbatch, the compatibility of the alkali masterbatch with the matrix is ​​improved, and the hole phenomenon caused by particle agglomeration in the low-weight film is avoided.

[0019] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0020] Preferably, the base resin includes EVA resin.

[0021] Preferably, the anti-PID masterbatch comprises zirconium phosphate masterbatch.

[0022] Preferably, the anti-hydrolysis masterbatch comprises EVA masterbatch of carbodiimide monomer and / or EVA masterbatch of polycarbodiimide.

[0023] Preferably, the modified alkali masterbatch comprises an EVA masterbatch of modified alkali.

[0024] Preferably, the raw materials for preparing the modified alkali EVA masterbatch include alkali powder, coupling agent, EVA resin and solvent.

[0025] Preferably, the preparation method of the modified alkali EVA masterbatch comprises the following steps:

[0026] (1) mixing alkali powder, coupling agent and solvent for the first time to obtain modified alkali powder;

[0027] (2) The modified alkali powder obtained in step (1) is mixed with EVA resin for a second time to obtain a premix, and the premix is ​​extruded and granulated by a twin-screw extruder to obtain EVA masterbatch of the modified alkali.

[0028] Preferably, the first mixing is to dissolve 0.1-0.3 parts of coupling agent (for example, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts or 0.3 parts, etc.) in 0.5-2 parts of solvent (for example, 0.5 parts, 1 parts, 1.5 parts or 2 parts, etc.) to obtain a diluted coupling agent solution, and then drop the diluted coupling agent solution into 95-100 parts of alkali powder (for example, 95 parts, 96 parts, 97 parts, 98 parts, 99 parts or 100 parts, etc.), and stir for 10-30 minutes (for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes, etc.) to obtain the alkali solution.

[0029] Preferably, the stirring is carried out in a high-speed mixer.

[0030] Preferably, the rotation speed of the high-speed stirrer is 1000-5000 r / min, for example, it can be 1000 r / min, 2000 r / min, 3000 r / min, 4000 r / min or 5000 r / min.

[0031] Preferably, the solvent comprises ethanol.

[0032] Preferably, the coupling agent is a silane coupling agent.

[0033] Preferably, the weight ratio of the alkali powder to EVA is 1:(9-19), for example, it can be 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18 or 1:19, etc.

[0034] Preferably, the alkali powder includes one or a combination of at least two of oxides, hydroxides or carbonates of alkaline earth metals, and more preferably, any one or a combination of at least two of magnesium oxide, calcium oxide, magnesium hydroxide and calcium hydroxide.

[0035] Preferably, the crosslinking agent includes any one of tert-butyl peroxide 2-ethylhexyl carbonate, tert-amyl peroxide 2-ethylhexyl carbonate, tert-butyl peroxide-3,5,5-trimethylhexanoate, di(4-methylbenzoyl)peroxide, dibenzoyl peroxide, 1,1-di(tert-butylperoxy)cyclohexane, n-butyl-4,4-di(tert-butylperoxy)valerate, diisopropylbenzene peroxide, α,α′-bis(tert-butylperoxy)-1,3-diisopropylbenzene or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, or a combination of at least two thereof.

[0036] Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, trimethylolpropane triacrylate, triallyl cyanurate, ethoxylated trimethylolpropane triacrylate or ethoxylated pentaerythritol tetraacrylate, or a combination of at least two thereof.

[0037] Preferably, the raw materials for preparing the encapsulation film further include any one of an antioxidant, a light stabilizer or a coupling agent, or a combination of at least two thereof.

[0038] Preferably, the content of the antioxidant in the raw materials for preparing the encapsulating film is 0.01-0.5 parts, for example, it can be 0.01 parts, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts.

[0039] Preferably, the content of the light stabilizer in the raw materials for preparing the encapsulating film is 0.05-0.2 parts, for example, it can be 0.05 parts, 0.07 parts, 0.1 parts, 0.12 parts, 0.15 parts, 0.17 parts, 0.2 parts, etc.

[0040] Preferably, the content of the coupling agent in the raw materials for preparing the encapsulation film is 0.2-0.6 parts, for example, it can be 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts or 0.6 parts.

[0041] Preferably, the antioxidant includes any one of hindered phenol antioxidants, aromatic amine antioxidants, phosphite antioxidants, thioether antioxidants or metal passivator antioxidants, or a combination of at least two thereof.

[0042] Preferably, the light stabilizer includes any one of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer or a hydroperoxide decomposer light stabilizer, or a combination of at least two of them.

[0043] Preferably, the coupling agent includes any one of a vinyl silane coupling agent, a chloroalkyl silane coupling agent, an aminoalkyl silane coupling agent, an epoxyalkyl silane coupling agent, a methacryloxyalkyl silane coupling agent, a sulfur-containing hydrocarbon silane coupling agent, a halogen silane coupling agent or a quaternary aminoalkyl silane coupling agent, or a combination of at least two thereof.

[0044] In a second aspect, the present invention provides a method for preparing the encapsulating film as described in the first embodiment, the preparation method comprising: mixing the raw material components in the encapsulating film, extruding and casting, and electron beam irradiation molding to obtain the encapsulating film.

[0045] Preferably, the mixing is carried out in a single screw extruder.

[0046] Preferably, the operating temperature of the single screw extruder is 60-100°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.

[0047] Preferably, the electron beam irradiation molding is performed in an electron irradiator.

[0048] Preferably, the operating voltage of the electron irradiator is 150-450Kv, for example, it can be 150Kv, 200Kv, 250Kv, 300Kv, 350Kv, 400Kv or 450Kv.

[0049] Preferably, the irradiation dose of the electron beam in the electron irradiator is 20-40 KGy, for example, it can be 20 KGy, 25 KGy, 30 KGy, 35 KGy or 40 KGy.

[0050] Preferably, the packaging film has a gram weight of 60-150 g / m 2 , for example, it can be 60g / m 2 , 80g / m 2 , 100g / m 2 , 120g / m 2 , 140g / m 2 or 150g / m 2 .

[0051] In a third aspect, the present invention provides an application of the encapsulation film as described in the first solution in busbar-free technology in the photovoltaic field.

[0052] Compared with the prior art, the present invention has at least the following beneficial effects:

[0053] (1) The present invention slows down the hydrolysis of the EVA substrate, reduces the generation of acidic substances, and improves the anti-PID performance of the film by adding anti-hydrolysis masterbatch, anti-PID masterbatch and modified alkaline masterbatch to the encapsulation film. At the same time, there is a synergistic effect between the anti-hydrolysis agent and the alkaline masterbatch, which can further absorb the acidic substances generated by hydrolysis, reduce the overall acidity of the film, and reduce the corrosion to the battery and the solder strip.

[0054] (2) The present invention improves the compatibility of the alkali masterbatch with the matrix by surface modification of the alkali masterbatch, thereby avoiding the hole phenomenon caused by particle agglomeration in the low-weight adhesive film. DETAILED DESCRIPTION

[0055] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] In the following specific implementation of the present invention, the specific information of the materials used is as follows:

[0057] 1. EVA resin: UL00628, purchased from Levitra Materials, VA content 28%, melt index 6g / 10min;

[0058] 2. Anti-PID masterbatch, zirconium phosphate masterbatch, purchased from Shanghai Langyi;

[0059] 3. Hydrolysis-resistant masterbatch 1: EVA masterbatch of carbodiimide monomer, purchased from Suzhou Keshengtong;

[0060] 4. Hydrolysis-resistant masterbatch 2: EVA masterbatch of polycarbodiimide, homemade, made by twin-screw extrusion granulation of polycarbodiimide and EVA resin UL00628 of Shanghai Youen Chemical at a weight ratio of 5:95.

[0061] Example 1

[0062] A packaging film, wherein the raw materials for preparing the packaging film include the following components in parts by weight:

[0063]

[0064] The preparation method of the modified alkali EVA masterbatch comprises the following steps: 100 parts of magnesium hydroxide powder are placed in a high-speed mixer at a stirring speed of 1000 r / min. 0.1 parts of KH570 are dissolved in 0.9 parts of ethanol to obtain a diluted coupling agent solution, and the diluted coupling agent solution is added dropwise to the high-speed mixer at a stirring speed of 5000 r / min, stirred for 20 minutes, and modified alkali powder is obtained. The modified alkali powder is mixed with EVA resin (Lianhong FL02528) in a weight ratio of 5:95, and then granulated by a twin-screw extruder to obtain the modified alkali EVA masterbatch.

[0065] The preparation method of the adhesive film comprises the following steps: 97 parts of EVA resin, 1 part of anti-PID masterbatch, 1 part of anti-hydrolysis masterbatch, 1 part of modified alkali EVA masterbatch, 0.5 part of cross-linking agent, 1 part of auxiliary cross-linking agent, 0.1 part of light stabilizer, and 0.5 part of silane coupling agent are uniformly mixed, extruded and casted in a single-screw extruder, and then irradiated and formed in an electron irradiator to obtain the packaging adhesive film.

[0066] The operating temperature of the single screw extruder was 80°C.

[0067] The operating voltage of the electron irradiator is 300Kv.

[0068] The irradiation dose of the electron beam in the electron irradiator is 30 KGy.

[0069] The weight of the film is 100g / m 2 .

[0070] Example 2

[0071] A packaging film, wherein the raw materials for preparing the packaging film include the following components in parts by weight:

[0072]

[0073] The preparation method of the modified alkali EVA masterbatch comprises the following steps: 98 parts of magnesium oxide powder are placed in a high-speed mixer at a stirring speed of 1000 r / min. 0.2 parts of coupling agent KH550 are dissolved in 1.5 parts of ethanol to obtain a diluted coupling agent solution, and the diluted coupling agent solution is added dropwise to the high-speed mixer at a stirring speed of 5000 r / min, and stirred for 30 minutes to obtain modified alkali powder. The modified alkali powder is mixed with EVA resin (Lianhong FL02528) at a weight ratio of 1:10, and then granulated by a twin-screw extruder to obtain the modified alkali EVA masterbatch.

[0074] The preparation method of the adhesive film comprises the following steps: uniformly mixing 100 parts of EVA resin, 2 parts of anti-PID masterbatch, 2.5 parts of anti-hydrolysis masterbatch, 2 parts of modified alkali EVA masterbatch, 1 part of cross-linking agent, 1.2 parts of auxiliary cross-linking agent, 0.2 parts of light stabilizer and 0.6 parts of silane coupling agent, extruding and casting through a single-screw extruder, and then irradiating and molding through an electron irradiator to obtain the packaging adhesive film.

[0075] The operating temperature of the single screw extruder was 90°C.

[0076] The operating voltage of the electron irradiator is 400Kv.

[0077] The irradiation dose of the electron beam in the electron irradiator is 40 KGy.

[0078] The weight of the obtained film is 120g / m 2 .

[0079] Example 3

[0080] A packaging film, wherein the raw materials for preparing the packaging film include the following components in parts by weight:

[0081]

[0082] The preparation method of the modified alkali EVA masterbatch comprises the following steps: 95 parts of calcium hydroxide powder are placed in a high-speed mixer at a stirring speed of 1000 r / min. 0.3 parts of coupling agent KH570 are dissolved in 2 parts of ethanol to obtain a diluted coupling agent solution, and the diluted coupling agent solution is added dropwise to the high-speed mixer at a stirring speed of 5000 r / min, stirred for 15 minutes, and modified alkali powder is obtained. The modified alkali powder is mixed with EVA resin (Lianhong FL02528) at a weight ratio of 1:15, and then granulated by a twin-screw extruder to obtain the modified alkali EVA masterbatch.

[0083] The preparation method of the adhesive film comprises the following steps: 95 parts of EVA resin, 0.8 parts of anti-PID masterbatch, 0.8 parts of anti-hydrolysis masterbatch, 0.8 parts of modified alkali EVA masterbatch, 0.3 parts of crosslinking agent, 1.2 parts of auxiliary crosslinking agent, 0.1 parts of light stabilizer, 0.2 parts of silane coupling agent, 0.05 parts of antioxidant are mixed evenly, extruded and casted in a single screw extruder, and then irradiated and formed in an electron irradiator to obtain the packaging adhesive film. The operating temperature of the single screw extruder is 70°C.

[0084] The operating voltage of the electron irradiator is 200Kv.

[0085] The irradiation dose of the electron beam in the electron irradiator is 20 KGy.

[0086] The weight of the film is 90g / m 2 .

[0087] Example 4

[0088] A packaging film, which is different from Example 1 in that: the content of the modified alkali EVA masterbatch in the raw materials for preparing the packaging film is 0.5 parts.

[0089] Example 5

[0090] A packaging film, which is different from Example 1 in that the content of the cross-linking aid in the raw materials for preparing the packaging film is 1.5 parts.

[0091] Comparative Example 1

[0092] A packaging film, which is different from Example 1 in that the EVA masterbatch of modified alkali is replaced by unmodified magnesium hydroxide (purchased from Hebei Meishen, high white and ultrafine).

[0093] Comparative Example 2

[0094] A packaging film, which is different from Example 1 in that: the raw materials used to prepare the packaging film do not contain an anti-hydrolysis agent.

[0095] Comparative Example 3

[0096] A packaging film, which is different from Example 1 in that: the raw materials for preparing the packaging film do not contain EVA masterbatch containing modified alkali.

[0097] Test Method

[0098] The adhesive film prepared by the present invention and the Daheng TOPCON battery are connected in series through the 0BB coating technology, and then ordinary adhesive films are laid, with the upper adhesive film Cybright T22h and the lower adhesive film Cybright T11 to make a double-glass component for testing.

[0099] PID192h attenuation (%): According to the standard "IEC 62804", the experimental temperature is 85℃, the relative humidity is 85%, and the time is 192h;

[0100] TC200h attenuation (%): Tested in accordance with IEC 61215, the test time is 200h;

[0101] DH1000h solder strip yellowing: Tested according to the test method provided in IEC 61215-2-2016, with the experimental temperature at 85°C and relative humidity at 85%;

[0102] Component EL: refer to "IEC 61215" and "IEC 61730" standards;

[0103] Pre-crosslinking degree: After the film is irradiated, it is cut into pieces and weighed (mass is M1), placed in a 120-mesh iron net (mass is M3), refluxed in xylene for 5 hours, taken out and dried and weighed (mass is M2), pre-crosslinking degree = [(M2-M3) / M1]×100%;

[0104] Film appearance: Observe whether there are holes on the film.

[0105] Test Results

[0106] The encapsulation films provided in Examples 1-6 and Comparative Examples 1-3 were tested according to the above test method. The test results are shown in Table 1:

[0107] Table 1

[0108]

[0109]

[0110] The test results show that:

[0111] (1) It can be seen from Examples 1 to 5 that the present invention slows down the hydrolysis of the EVA substrate, reduces the generation of acidic substances, and improves the anti-PID performance of the film by adding anti-hydrolysis masterbatch, anti-PID masterbatch and modified alkali EVA masterbatch to the encapsulation film. The component PID decays <2% in 192h, TC decays <2.5% in 200h, and the DH1000h solder strip has no yellowing phenomenon.

[0112] (2) It can be seen from Example 1 and Comparative Example 1 that when the EVA masterbatch of the modified alkali is replaced with unmodified magnesium hydroxide particles in the encapsulation film prepared by the present invention, the anti-PID effect and TC200h effect of the component become worse, the film is obviously damaged, and the EL of the component is shadowed, which cannot meet the actual use requirements.

[0113] (3) It can be seen from Example 1 and Comparative Examples 2-3 that when the raw materials for preparing the encapsulating film prepared by the present invention do not contain an anti-hydrolysis agent or an EVA masterbatch containing a modified alkali, the soldering tape of the DH1000h component turns yellow and the anti-PID performance is severely cracked, which cannot meet the actual use requirements.

[0114] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A packaging film, characterized in that: The raw materials for preparing the encapsulation film include the following components by weight:

2. The packaging film according to claim 1, characterized in that: The base resin includes EVA resin.

3. The packaging film according to claim 1 or 2, characterized in that: The anti-PID masterbatch comprises zirconium phosphate masterbatch.

4. The packaging film according to any one of claims 1 to 3, characterized in that: The anti-hydrolysis masterbatch includes EVA masterbatch of carbodiimide monomer and / or EVA masterbatch of polycarbodiimide.

5. The packaging film according to any one of claims 1 to 4, characterized in that: The modified alkali masterbatch comprises an EVA masterbatch of modified alkali; Preferably, the raw materials for preparing the modified alkali EVA masterbatch include alkali powder, coupling agent, EVA resin and solvent.

6. The packaging film according to any one of claims 1 to 5, characterized in that: The preparation method of the modified alkali EVA masterbatch comprises the following steps: (1) mixing alkali powder, coupling agent and solvent for the first time to obtain modified alkali powder; (2) mixing the modified alkali powder obtained in step (1) with EVA resin for a second time to obtain a premix, and the premix is ​​extruded and granulated by a twin-screw extruder to obtain EVA masterbatch of the modified alkali; Preferably, the first mixing is to dissolve 0.1-0.3 parts of the coupling agent in 0.5-2 parts of the solvent to obtain a diluted coupling agent solution, and then drop the diluted coupling agent solution into 95-100 parts of the alkali powder, stirring for 10-30 minutes, to obtain the modified alkali powder; Preferably, the stirring is carried out in a high-speed mixer; Preferably, the rotation speed of the high-speed stirrer is 1000-5000r / min; Preferably, the solvent comprises ethanol; Preferably, the coupling agent is a silane coupling agent; Preferably, the weight ratio of the alkali powder to EVA is 1:(9-19); Preferably, the alkali powder includes one or a combination of at least two of oxides, hydroxides or carbonates of alkaline earth metals, and more preferably, any one or a combination of at least two of magnesium oxide, calcium oxide, magnesium hydroxide and calcium hydroxide.

7. The packaging film according to any one of claims 1 to 6, characterized in that: The cross-linking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, tert-butyl peroxy-3,5,5-trimethylhexanoate, di(4-methylbenzoyl) peroxide, dibenzoyl peroxide, 1,1-di(tert-butylperoxy)cyclohexane, n-butyl-4,4-di(tert-butylperoxy)valerate, diisopropylbenzene peroxide, α,α′-bis(tert-butylperoxy)-1,3-diisopropylbenzene or 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, or a combination of at least two thereof; Preferably, the auxiliary cross-linking agent includes any one of triallyl isocyanurate, trimethylolpropane triacrylate, triallyl cyanurate, ethoxylated trimethylolpropane triacrylate or ethoxylated pentaerythritol tetraacrylate, or a combination of at least two thereof.

8. The packaging film according to any one of claims 1 to 7, characterized in that: The raw materials for preparing the encapsulation film further include any one of an antioxidant, a light stabilizer or a coupling agent, or a combination of at least two thereof; Preferably, the content of antioxidant in the raw materials for preparing the encapsulation film is 0.01-0.5 parts; Preferably, the content of the light stabilizer in the raw materials for preparing the encapsulation film is 0.05-0.2 parts; Preferably, the content of the coupling agent in the raw material for preparing the encapsulation film is 0.2-0.6 parts; Preferably, the antioxidant includes any one of a hindered phenol antioxidant, an aromatic amine antioxidant, a phosphite antioxidant, a thioether antioxidant or a metal passivator antioxidant, or a combination of at least two thereof; Preferably, the light stabilizer includes any one of a light shielding agent light stabilizer, a quencher light stabilizer, a free radical scavenger light stabilizer or a hydroperoxide decomposer light stabilizer, or a combination of at least two thereof; Preferably, the coupling agent includes any one of a vinyl silane coupling agent, a chloroalkyl silane coupling agent, an aminoalkyl silane coupling agent, an epoxyalkyl silane coupling agent, a methacryloxyalkyl silane coupling agent, a sulfur-containing hydrocarbon silane coupling agent, a halogen silane coupling agent or a quaternary aminoalkyl silane coupling agent, or a combination of at least two thereof.

9. A method for preparing the encapsulation film according to claims 1-8, characterized in that: The preparation method comprises: mixing various raw material components in the packaging film, extruding and casting, and electron beam irradiation molding to obtain the packaging film; Preferably, the mixing is carried out in a single screw extruder; Preferably, the operating temperature of the single screw extruder is 60-100°C; Preferably, the electron beam irradiation molding is carried out in an electron irradiator; Preferably, the operating voltage of the electron irradiator is 150-450Kv; Preferably, the irradiation dose of the electron beam in the electron irradiator is 20-40KGy; Preferably, the packaging film has a gram weight of 60-150 g / m 2 .

10. Application of the encapsulation film according to claims 1-8 in busbar-free technology in the photovoltaic field.

Citation Information

Patent Citations

  • Low-gram-weight adhesive film for main-grid-free photovoltaic module and preparation method of low-gram-weight adhesive film

    CN117701189A